Comparison of In Vivo Stiffness of Tendons Commonly Used for Anterior Cruciate Ligament Reconstruction – A Shear Wave Elastography Study - Pasurka, Mario; Falck, Theo; Kubach, Joshua; Simon, Michael; Söllner, Stefan; Strobel, Deike; Perl, Mario; Betsch, Marcel (Academic Radiology, 2024)
Rationale and Objectives: There are currently no studies investigating the in vivo stiffness of the most commonly used autografts for anterior cruciate ligament reconstruction (ACLR) using Shear wave elastography (SWE). We hypothesize that there are differences regarding the elastic properties between the three tendons commonly used for ACLR and that they are influenced by patient-related factors. Materials and Methods: 80 healthy subjects (25 females, 55 males, age: 25.33 ± 4.76 years, BMI: 23.76 ± 3.14 kg/m2, 40 semiprofessional athletes, athlete group [AG], age: 25.51 [19–29]; 40 healthy controls, control group [CG], age: 25.50 [20–29]) were recruited as participants. In addition to patient reported outcome scores, every participant underwent a standardized multimodal ultrasound protocol consisting of B-mode-ultrasound (B-US), Color Doppler-ultrasound (CD-US) and a SWE examination of the bilateral quadriceps tendon (QT), patellar tendon (PT) and semitendinosus tendon (ST). Results: The highest shear wave velocity (SWV) were observed in ST (4.88 (4.35–5.52) m/s, ST vs QT, p = 0.005; ST vs PT, p < 0.001) followed by QT (4.61 (4.13–5.26) m/s, QT vs PT, p < 0.001) and PT (3.73 (3.30–4.68) m/s). Median QT, PT and ST stiffness was significantly higher in AG compared to CG. Male subjects tend to have stiffer QT and PT than female subjects. Positive correlation with SWV was obtained for age and activity level. Conclusion: There are significant differences regarding in vivo tendon stiffness between the most frequently used autograft tendon options for ACLR. The quantitative information obtained by SWE could be of particular interest for graft choice for ACLR.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Musculoskeletal ultrasound; Shear wave elastography; Tendon stiffness

Efficacy of a new treatment algorithm for capsulitis of the fingers in rock climbers - Schöffl, Volker Rainer; Lutter, Christoph; Lang, Hans Christoph; Perl, Mario; Moser, Othmar; Simon, Michael (Frontiers in Sports and Active Living, 2025)
Background: Although finger joint capsulitis has been described among the most frequent injuries in climbers, no clinical studies on treatment strategies and outcomes are available. Study design: Prospective case series study. Methods: Between 2015 and 2018 we prospectively treated 50 patients (38 male, 12 female) with a total number of 69 independent finger joint capsulitis according to a clinic specific treatment regimen and evaluated the outcome retrospectively. Therapy consisted of either conservative management, steroid injections, radiosynoviorthesis or a combination depending on the treatment regimen, prior therapy and timeline of symptoms. Outcomes were assessed using visual analogue scale (VAS), Buck-Gramcko score and a climbing specific outcome score with secondary patient recall. Results: The proximal interphalangeal joint of the middle finger was the most commonly affected joint, and there was no correlation with osteoarthritis. All climbers returned to sport within 12 months. The majority were able to maintain their level of performance after injury and the difference in climbing level before and after injury was not statistically significant (p = 0.22). The total time spent climbing was significantly less after the injury than before the injury (p < 0.001). The Buck-Gramcko score showed excellent results. The overall functional outcome was good to very good with a mean score of 1.6 ± 0.7, as was the climbing specific score of 1.7 ± 0.9. Pain was significantly less after treatment than before (p < 0.001). Conclusion: Good to very good functional and sport-specific outcomes were seen with the stage-specific treatment regimen presented, allowing all patients studied to resume climbing. A better understanding of the underlying pathogenesis is essential in order to better assess long-term progress.
CRIS-Team Scopus Importer:2025-02-14
Keywords: capsulitis; finger injuries; finger joint synovitis; rock climbing; sport climbing

Functional and Sport-Specific Outcome Following Traumatic First-Time Shoulder Dislocation and Arthroscopic Surgical Repair in Rock Climbers - Simon, Michael; Geffel, Leonid; Lutter, Christoph; Schöffl, Volker Rainer (Wilderness & Environmental Medicine, 2023)
Introduction: Traumatic shoulder dislocations rank among the most common shoulder injuries in climbers, with rising numbers over the last years. The objective of this study was to analyze the outcome following traumatic first-time shoulder dislocation and subsequent surgical treatment in this population. Methods: In a retrospective study, climbers who experienced a traumatic shoulder dislocation were treated with an arthroscopic repair of the labrum-ligament complex (LLC). The functional outcome was assessed with a standardized questionnaire and clinical examination, including the Constant Murley and Single Assessment Numeric Evaluation scores. The sport-specific outcome was analyzed using the Union Internationale des Associations d'Alpinisme (UIAA) scale of difficulty and a sport-specific outcome score. Results: The functional and sport-specific outcome for 27 climbers (20 men; 7 women; 3 with bilateral injuries; age, 34±11 [17–61] y; data presented as mean±SD [range]) was assessed 53±29 (12–103) mo after surgery. The postoperative Constant Murley score was 95±8 (67–100) points. At follow-up, 93% (n=25) of patients had started climbing again. Twenty-one climbers (78%) reached a climbing level within the range of ±0.33 UIAA grades of their initial capability or even exceeded their preinjury grade. Only 7% (n=2) of the patients had a recurrent shoulder dislocation, leading to a secondary surgery, and, therefore, required ongoing postoperative treatment at the time of follow-up. Conclusions: Arthroscopic repair of the LLC following first-time traumatic shoulder dislocation in climbers shows a good outcome and a low recurrence rate. After surgery, most patients are able to regain a high level of rock-climbing ability.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Bankart lesion; labrum-ligament complex repair; shoulder surgery; sports injuries

Patellaosteotomie kombiniert mit modifizierter Trochleaplastik und Tuberositasmedialisierung als Therapie der permanenten Patellaluxation in Beugung - Dickschas, Jörg; Schmeling, Arno; Perl, Mario; Simon, Michael (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
CRIS-Team Scopus Importer:2023-09-15

Transtuberositary, Anterior Open Wedge High Tibial Osteotomy (TT-AOW-HTO) to Correct a Negative Slope Transtuberositäre, ventral öffnende hohe Tibiaosteotomie zur Korrektur eines negativen Slope - Harrer, Jörg; Ferner, Felix; Lutter, Christoph; Petersen, Wolf; Perl, Mario; Simon, Michael (Zeitschrift für Orthopädie und Unfallchirurgie, 2025)
CRIS-Team Scopus Importer:2025-02-28